Effect of acceptance of disease on quality of life in patients with chronic obstructive pulmonary disease - Olek, Dominika; Uchmanowicz, Izabella; Chudiak, Anna; Jankowska-Polańska, Beata (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. Chronic obstructive pulmonary disease affects the quality of life and has a close relationship with the level of acceptance of the disease. Increasing acceptance of the disease may increase to adapt to COPD and affect a more active dealing with this condition. Material and methods. The research was conducted among 100 people aged from 31 to 80 years old diagnosed with chronic obstructive pulmonary disease. The study used a scale of acceptance of disease AIS, the quality of life of the general questionnaire SF-36 and questionnaire by your own. Aim. Assessment of the effects of the acceptance of the disease on quality of life of patients with COPD. Results. A person at the age of 71–80 is much more accepting of their illness than younger people. People working physically are characterized by higher levels of the scale of acceptance of disease than persons who are in the pension or retirement. Men have a more physical dimension value and the quality of life index, and therefore the worse quality of life than women. Conclusions. A person under the age of 50 years, determine its quality of life as better compared to those over 50 years of age. The increase in the level of acceptance of the disease affects the improvement of the quality of life in all dimensions. Nursing Topics 2014; 22 (4): 471–476